2015
DOI: 10.1155/2015/106836
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Hydrogen-Rich Saline on Rats with Smoke Inhalation Injury

Abstract: Objective. To explore the protective effects of hydrogen-rich saline on rats with smoke inhalation injury. Methods. 36 healthy male Sprague-Dawley rats were randomly divided into 3 groups (n = 12 per group): sham group (S), inhalation injury plus normal saline treatment group (I+NS), and inhalation injury plus hydrogen-rich saline treatment group (I+HS). 30 min after injury, normal saline and hydrogen-rich saline were injected intraperitoneally (5 mL/kg) in I+NS group and I+HS group, respectively. All rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Cytokines released excessively can cause acute lung injury in patients. An increase in TNF-α levels will lead to the activation of inflammatory cytokines such as IL-1, IL-6, and IL-8 ( Chen et al, 2015 ). At the same time, high mobility group box1 (HMGB1) ( Ma et al, 2015 ), CCL2 ( Hillman et al, 2007 ), and Egr-1 ( Hoetzel et al, 2008 ) all affect the release of inflammatory factors.…”
Section: Hydrogen and The Cytokine Stormmentioning
confidence: 99%
“…Cytokines released excessively can cause acute lung injury in patients. An increase in TNF-α levels will lead to the activation of inflammatory cytokines such as IL-1, IL-6, and IL-8 ( Chen et al, 2015 ). At the same time, high mobility group box1 (HMGB1) ( Ma et al, 2015 ), CCL2 ( Hillman et al, 2007 ), and Egr-1 ( Hoetzel et al, 2008 ) all affect the release of inflammatory factors.…”
Section: Hydrogen and The Cytokine Stormmentioning
confidence: 99%
“…Mucociliary clearance is markedly increased in rats with average particulate matter cleared from the lung within 8 h, although this process can take in excess of 24 h in humans [240]. Other disadvantages to using rat models include the fact that they are obligate nose breathers [235], possess no goblet cells [23], and possess significantly fewer mucosal glands than larger animals, rendering chronic bronchitis modeling difficult [242]. Guinea Pigs Guinea pigs have been studied extensively in respiratory experimentation, particularly in the field of tuberculosis [243][244][245].…”
Section: Ratsmentioning
confidence: 99%
“…Studies have also shown that H 2 improves lung injuries induced by many other factors, such as hyperoxia [ 163 , 164 ], lipopolysaccharides [ 14 , 17 ], smoke inhalation [ 165 ], paraquat[ 166 ], monocrotaline [ 167 ], and extensive burns [ 168 ]. A 2013 study showed that HS pretreatment ameliorated cigarette smoking-induced airway mucus production and airway epithelium damage in rats [ 169 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%